Climate action through policy expansion and/or dismantling: country-comparative insights : an introduction to the special issue - Bulian, Simon; Tosun, Jale; Jordan, Andrew J. (Journal of comparative policy analysis, 2024)
Elected politicians and civil servants are key in developing climate policy. The articles in this special issue investigate factors that induce politico-administrative actors to adopt climate policies and dismantle anti-climate policies to advance decarbonisation. Politico-administrative actors have predominantly expanded climate policy and raised policy ambition in recent decades. However, economic crises and weakening public support may cause dismantling of climate policy and hamper policy ambition. Against this backdrop, articles in this special issue also study factors that propel climate policy dismantling. Together, the contributions show that interactions between politico-administrative actors and publics, organised interests, and international organisations shape climate and anti-climate policy change.
Gesehen am 07.01.2025